Use and impact of social prescribing: a mixed-methods feasibility study protocol - Uy Hoang; Harshana Liyanage; Simon de Lusignan; Victoria Tzortziou Brown; Filipa Ferreira; Ivelina Yonova; Lucy Moore; Anant Jani (BMJ Open)
Introduction Social prescribing aims to address social determinants of health, which account for 80%–90% of health outcomes, but the evidence base behind it is limited due to a lack of data linkingsocial prescribing activity and outcomes.Methods and analysis The objective of the quantitative component of this feasibility studyisto identify the characteristics of individuals who receive social prescriptions and describe the use and estimate the impact of social prescribing; the latter will be done on a homeless subgroup. We will use the Oxford Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) primary care sentinel network, whose general practicescover a population of over 4 000 000 patients. Social prescribing data will be extracted onall recorded patients for 5 years up to 31 January 2020. The objective for the qualitative component of the study isto explore approaches to understand the contextual factors that will have influenced our quantitative findings to identify mechanisms to encourage adoption of social prescribing in primary care while improving data quality. Itwill comprise up to three 90–120 minute advisory group meetings for six to eight participants. Participants will be recruited based on their experience of delivering primary care within Oxfordshire and Surrey. The advisory group outputs will be analysed using framework analysis and will be used to create a survey instrument consisting of statements that surveyees, who will consist of primary care practitioners within the RCGP RSC, can agree or disagree with.Ethics and dissemination All RCGP RSC data are pseudonymised at the point of data extraction. No personally identifiable data are required for this investigation. This protocol follows the Good Reporting of a Mixed Methods Study checklist. The study results will be published in a peer-reviewed journal and the dataset will be available to other researchers.